Light-induced differences in conformational dynamics of the circadian clock regulator VIVID - Lee, Chung-Tien; Malzahn, Erik; Brunner, Michael; Mayer, Matthias P. (Journal of molecular biology, 2014)
The LOV (light-oxygen-voltage) domain protein VIVID (VVD) is a negative regulator of the circadian transcription factor White Collar Complex and controls light response and photoadaptation in Neurospora. Blue light converts VIVID from the dark state into the light state (VVDL) with concomitant homodimerization. Upon return to low-light conditions, VVD very slowly reverts back into the monomeric dark state (VVDD). To better understand the nature of the conformational changes that are the basis for the light-dark switch in VVD, we used hydrogen exchange mass spectrometry to probe solvent accessibility of backbone amide protons. Our data demonstrate that all structural elements of VVDD except for the N-cap region exchange according to the rare EX1 mechanism indicating a reversible unfolding with rather slow refolding rate. Interestingly, the unfolding halftimes of different elements were not identical but varied from 400 to 900s. VVDL also exchanges according to the EX1 mechanism, albeit with a halftime of 6h. Surprisingly, the dimerization interface showed very little protection suggesting a rapid dimer-monomer interconversion.
Online 2 November 2013
Gesehen am 06.10.2020